2016
DOI: 10.1155/2016/3174841
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Aqueous Extract of Cinnamon on the Metabolome ofPlasmodium falciparumUsing1HNMR Spectroscopy

Abstract: Malaria is responsible for estimated 584,000 deaths in 2013. Researchers are working on new drugs and medicinal herbs due to drug resistance that is a major problem facing them; the search is on for new medicinal herbs. Cinnamon is the bark of a tree with reported antiparasitic effects. Metabonomics is the simultaneous study of all the metabolites in biological fluids, cells, and tissues detected by high throughput technology. It was decided to determine the mechanism of the effect of aqueous extract of cinnam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
1
17
1
3
Order By: Relevance
“…Despite implementing current best practices, including erythrocyte lysis and washing steps to remove parasites from their intracellular milieu ( Fig. 1A, (3,8,12,22)), parasite separation from the host is poor. Microscopy revealed that parasites lysed from host cells remain embedded in erythrocyte membranes and washes fail to isolate parasite material ( Fig.…”
Section: Metabolomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite implementing current best practices, including erythrocyte lysis and washing steps to remove parasites from their intracellular milieu ( Fig. 1A, (3,8,12,22)), parasite separation from the host is poor. Microscopy revealed that parasites lysed from host cells remain embedded in erythrocyte membranes and washes fail to isolate parasite material ( Fig.…”
Section: Metabolomicsmentioning
confidence: 99%
“…We found that extra-parasite material contributed by host erythrocytes and media components can also heavily impact the metabolome. Many studies employ erythrocyte lysis prior to sample purification ( (3,8,12,22), see Materials and Methods). However, several novel results from our study show that this step does not eliminate the potential for host contamination.…”
Section: Metabolome Interpretation Is Normalization-approach Dependenmentioning
confidence: 99%
See 1 more Smart Citation
“…C. verum has several medicinal properties, such as anti-inflammatory, hypoglycemic, antibacterial, antioxidant, spasmolytic, antidiarrheal, antifungal, antitumor, analgesic, gastroprotective, anticancer, and anthelmintic ones [14,19,20]. Interestingly, recent studies have documented the antimalarial efficacy of C. verum extract [21,22]. However, to our knowledge, no data has been reported to show the efficacy of C. verum herbal extracts against the growth of piroplasm parasites.…”
Section: Introductionmentioning
confidence: 99%
“…The P. falciparum genome is poorly annotated (40% of genes) compared to many model organisms (85% of genes for S. cerevisiae), making metabolomics an attractive method for unbiased study of parasite biology (7,8). Indeed, Plasmodium metabolomics has become increasingly popular in recent years for investigation of parasite biology and antimalarial drug action (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%